Pedagogical strategy of teacher training from a perspectiva desarrolladora - Nieva Chaves, José Antonio
This article presents partially the results of the doctoral research, concluded, entitled “Estrategia pedagógica de formación docente orientada al Aprendizaje Significativo Desarrollador de los instructores del SENA”. The structural and functional components of the strategy are presented, as well as their interrelationships from a holistic view, which were collectively constructed in the dialectic between theory and practice, with emphasis on participatory action research. It is the result of a teacher training from the vigotskian historical cultural approach and the meaningful learning of Ausubel.